Cost effectiveness between crop-livestock integration and non-crop-livestock integration in oil palm plantation case study at Ladang Risda Durian Mas / Ahmad Shahrizam Mohamad - Mohamad, Ahmad Shahrizam (Faculty of Plantation and Agrotechnology, 2018)
This study was conducted to determine the comparison in cost of two different plantation system which is crop-livestock integration which makes cattle as a source of integration and the other one is non-crop livestock integration which has zero number of cattle in the field. The objective is to determine which system is better in cost, profit and loss of the estate. Obviously, the major concern of this system is to gain higher income for estate while reducing other operation cost such as manuring and spraying. The secondary data was collected in 5 years from 2013 until 2017 at Ladang Risda Durian Mas, Terengganu. The data consists of spraying cost, manuring cost, labour cost, cattle cash flow and fresh fruit bunch (FFB) revenue. The data was analysed using enterprise budget to determine the profit and loss for both systems. Based on enterprise budget, it is identified that in Block A (integration system), the net income per hectare from 2013 until 2017 is RM5629.88, RM7815.90, RM8181.12, RM11862.00 and RM12685.07 respectively. In Block B (non-integration system) the net income per hectare is RM4102.43, RM5207.49, RM5491.91, RM9200.96 and RM9740.58 respectively. From this result, there is a significant difference in both systems in net income. For total cost per hectare from the year 2013 until 2017, it is identified that in Block A is RM3740.15, RM2532.16, RM2725.48, RM2377.91 and RM1167.13. In Block B, the total cost per hectare is RM3006.04, RM2390.43, RM2598.36, RM2073.88, and RM906.32. From this result, there is significant difference of costing for crop-livestock integration system and non-crop-livestock integration